THE INFLUENCE OF BASRENG PRODUCT INNOVATION ON THE COMPETITIVENESS OF THE UD SANJAYA SOUTH LAMPUNG (NATAR) FOOD FACTORY - Jihan Indrianti Putri; M. Oktaviannur (ZILLZELL MEDIA PRIMA, 2025)
One of the snack manufacturers in South Lampung, particularly in the Natar region, where the snack sector is highly competitive, is UD Sanjaya. The purpose of this study is to examine how the competitiveness of the UD Sanjaya food factory in South Lampung, Natar, is impacted by product innovation, product quality, and basreng design. The author bases the question,